Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Kekerasan Seksual - Syuha Maisytho Probilla; Andi Najemi; Aga Anum Prayudi (Fakultas Hukum, Universitas Jambi, 2021)
This article explains 1) Child as victim of sexual violence in the case of WA did not obtain legal protection as from the beginning the victim was declared as the perpetrator rather than as a victim. The victim was granted status as the perpetrator until the court verdict imposed a crime and the victim had served the sentence at LPKA. The victim received post-adjudication legal assistance after being accompanied by a Legal Counsel. 2) The obstacles faced so that child victims did not obtain legal protection is due to the lack of sensitivity by the UPTD PPA in understanding the